Edaravone dexborneol attenuates oxidative stress in experimental subarachnoid hemorrhage via Keap1/Nrf2 signaling pathway - Kunyuan Zhu; Kunyuan Zhu; Shijun Bi; Zechao Zhu; Zechao Zhu; Wenxu Zhang; Wenxu Zhang; Xinyu Yang; Xinyu Yang; Jiashuo Li; Guobiao Liang; Chunyong Yu; et al. (Frontiers Media S.A., 2024)
BackgroundSubarachnoid hemorrhage (SAH) serves as a disease characterized by high incidence rate, which is exceedingly prevalent and severe. Presently, there is no unambiguous or efficacious intervention for the neurological impairment following SAH. Administering multi-targeted neuroprotective agents to reduce oxidative stress (OS) and neuroinflammation caused by early brain injury (EBI) has been demonstrated to improve neurological function and prognosis following SAH. Edaravone dexborneol (EDB), a novel multi targeted neuroprotective medication, combines four parts edaravone (EDA) with 1 part (+)-borneol in proportion. Clinical trials conducted in China have revealed during 2 days of acute ischemic stroke (AIS), early administration of EDB leads to improved therapeutic outcomes compared to treatment in EDA monotherapy. Currently, there is no clear evidence that EDB can effectively treat SAH, therefore, our study aims to investigate its potential therapeutic effects and mechanisms on EBI after SAH.MethodWe used the intravascular threading method to establish a mouse model of SAH to explore whether EDA and EDB could produce anti-OS and anti-apoptosis effects. Behavioral assessment of mice was conducted using the balance beam experiment and the modified Garcia scoring system. Neuronal damage due to OS and Keap1/Nrf2 signaling pathway were detected through techniques of immunofluorescence, Western blotting, spectrophotometry. The group of EDA and EDB were injected intraperitoneally for 72 h after SAH.ResultsThe experiment results indicated that EDB lead to remarkably positive results by significantly enhancing neurological function, reducing blood-brain barrier (BBB) injury, and effectively inhibiting neuronal apoptosis after SAH. Further examination indicated EDB significantly reduced the expression of Keap1 and increased the expression of Nrf2, and it inhibited MDA, and enhanced SOD activity after SAH. These outcomes surpassed the effectiveness observed in EDA monotherapy. However, the application of ML385 reversed the anti-OS effects of EDB and EDA.ConclusionOur experimental findings indicated that EDB could activate Keap1/Nrf2 signaling pathway to reduce OS damage, thereby protecting neurological function and enhancing behavioral abilities after SAH. These outcomes could facilitate the creation of new approaches for the clinical management of SAH.